Gas discharge visualisation technology for psychological research applications: A systematic review - Raul Valverde; Konstantin G. Korotkov (International Journal of Studies in Psychology, 2025)
Gas discharge visualisation (GDV) is a nonintrusive technique that captures a person's physiological and psychoemotional status, including stress. This is through the electro-photonic emissions of fingertips placed on the surface of an impulse analyser. This study is to systematically review the GDV for psychological research applications through the PRISMA-NMA method. For the literature search, three databases, DOAJ, Scopus, and WOS, were consulted, using keyword terms, which allowed working with 20 articles published from 2002 to Feb 2025, demonstrating empirical evidence of the impact of GDV for psychological applications.